Forensic Investigation of Stainless Steel 316 Hydrogen-Membrane and Ammonia-Cracking Reactors Through Mechanical Testing - Alexander Ilyushechkin; Veronica Gray; Riley Ingle; Lachlan Carter; Liezl Schoeman (Corrosion and Materials Degradation)
Knowledge of alloy behavior under industry-relevant conditions is critical to hydrogen production and processing, yet it is currently limited. To understand more about the impact of hydrogen damage on stainless steel 316 under realistic in-service conditions, we conducted a forensic investigation of two reactors exposed to various hydrogen-processing conditions. We examined samples of reactor walls exposed to hydrogen-containing atmospheres for >100 and ~1000 h at elevated temperatures during hydrogen separation and ammonia cracking. The samples were characterized by tensile testing, stretch–bend testing, and three-point bending. A loss in ductility and strength was observed for the reactor wall material compared with both untreated materials and materials annealed in neutral atmospheres at the same temperatures used during reactor operation. The three-point bend testing, which was conducted on inner and outer pipe-surface material extracted via electrical discharge machining, showed larger changes in the flexural modulus of exposed reactors but increases in the elastic limit. Microstructural observations revealed that hydrogen may play a role in stress relaxation, possibly promoting normalization at lower-than-expected temperatures. We also observed that materials exposed to ammonia undertake more damage from nitriding than from hydrogen.